1996
DOI: 10.1089/jir.1996.16.489
|View full text |Cite
|
Sign up to set email alerts
|

The Biologic Activity and Molecular Characterization of a Novel Synthetic Interferon-Alpha Species, Consensus Interferon

Abstract: Consensus interferon (Infergen) is a wholly synthetic type I interferon (IFN), developed by scanning several interferon-alpha nonallelic subtypes and assigning the most frequently observed amino acid in each position, resulting in a consensus sequence. The antiviral, antiproliferative, NK cell activation activity, cytokine induction, and interferon-stimulated gene-induction activity of consensus interferon has been compared with naturally occurring type I interferons. In all of these comparisons, consensus int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
113
0
2

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 183 publications
(120 citation statements)
references
References 47 publications
5
113
0
2
Order By: Relevance
“…IFN alfacon-1 (Infergen, Intermune Corp, Brisbane, California), a synthetic IFN-α designed to represent a consensus , has been shown in both cell culture systems [21] and comparative clinical trials [22] to inhibit viral replication more potently than other IFN-αs. Based on these findings, a pilot study to evaluate the potential clinical benefit and safety of IFN alfacon-1 in SARS treatment was conducted by our laboratory.…”
Section: Introductionmentioning
confidence: 99%
“…IFN alfacon-1 (Infergen, Intermune Corp, Brisbane, California), a synthetic IFN-α designed to represent a consensus , has been shown in both cell culture systems [21] and comparative clinical trials [22] to inhibit viral replication more potently than other IFN-αs. Based on these findings, a pilot study to evaluate the potential clinical benefit and safety of IFN alfacon-1 in SARS treatment was conducted by our laboratory.…”
Section: Introductionmentioning
confidence: 99%
“…More than 75% of patients in western Europe are infected with genotype 1 often showing a high viral load and these patients are so called "difficult to treat" and therefore remain at risk not to respond to standard HCV treatments [5] . Before pegylated IFN was available, we introduced a study using IFN-alfacon-1, a second-generation cytokine that was engineered to contain the most frequently occurring amino acids among the non-allelic IFN-α subtypes in humans [6] . In vitro studies showed that IFNalfacon-1 induces a more dramatic decrease of HCV-RNA compared to IFN-2b [7] and shows a 10-time higher antiviral efficacy [6] .…”
Section: Introductionmentioning
confidence: 99%
“…Before pegylated IFN was available, we introduced a study using IFN-alfacon-1, a second-generation cytokine that was engineered to contain the most frequently occurring amino acids among the non-allelic IFN-α subtypes in humans [6] . In vitro studies showed that IFNalfacon-1 induces a more dramatic decrease of HCV-RNA compared to IFN-2b [7] and shows a 10-time higher antiviral efficacy [6] . The rationale for daily dosing in our study was the fact that serum levels of IFN-α given three times a week were dropping almost below the detection limit every other day and therefore reducing the antiviral capability.…”
Section: Introductionmentioning
confidence: 99%
“…Patients were treated feron by assigning the most commonly observed amino acid in each position to generate a consensus sequence. 16,17 A with the study drug administered subcutaneously three times weekly for 24 weeks. Treatment was then stopped, and pasynthetic complementary DNA sequence was constructed and transfected into Escherichia coli.…”
mentioning
confidence: 99%
“…Assessable liver biopsy specimens were available from 594 of the 704 randomized alpha interferons. 16 patients (84%) before the administration of the study drug.…”
mentioning
confidence: 99%